ARTIFICIAL INTELLIGENCE AS A CREATIVE COLLABORATOR IN CONTEMPORARY VISUAL AND PERFORMING ARTS - P, Pushpalatha; Sripada, Pushpa Nagini; M, Vinitha; N, Muninathan; Packirisamy, Subbulakshmi; Yu Yang (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The use of artificial intelligence in modern art is gaining more and more popularity; machines are able to produce visual data and be involved in creative processes. This paper examines how artificial intelligence is used as a creative partner in contemporary visual arts, specifically how generative models can support artists in the design of the concept and exploration of the artistic process. To encourage human-AI co-creation, a collaborative model that combines data preparation, generative AI models, interactive user interfaces and rendering modules is suggested. A dataset of 10,000 digital artworks that represent a variety of artistic styles was used to evaluate the experimentation. A generative model that runs on diffusion has been used to generate visual compositions in response to artist prompts. Findings show that AI-guided creative processes are highly time-saving and enhance the production time of artwork, as well as, stylistic and conceptual range. The comparative analysis shows that the rating of visual quality and artist satisfaction improves in case AI tools are introduced to the creative process. The results also demonstrate the possibility of artificial intelligence as a creative companion that can make humans more creative instead of stealing artistic status. The suggested framework helps in the evolving body of computational creativity because it will show how intelligent systems can supplement artistic processes and contribute to interactive creation of visual arts. The research offers information on how generative AI can be integrated into artistic space and outlines the future research prospects of immersive and interactive systems based on AI using creativity.